ANALISIS PENERAPAN SISTEM PENGENDALIAN INTERN TERHADAP KINERJA DAN PENERIMAAN RETRIBUSI PARKIR DI DINAS PERHUBUNGAN KOTA MANADO - Munaiseche, Claudio V.; Ilat, Ventje; Lambey, Robert (Universitas Sam Ratulangi, 2018)
Internal control systems are needed for every government agency from planning, supervision, to accountability, must be carried out in an orderly, controlled, efficient and effective. So that the performance of government agencies is directed and reaches the goal. This study aims to determine whether the implementation of the internal control system on the performance and retribution parking income at the Manado city transportation office is adequate or inadequate. This research method is a qualitative descriptive study. Based on the results of the research and discussion, it can be seen that the internal control system on the performance and retributionÂ parking income at Transportation department of at Manado city has been